2020
DOI: 10.1177/1460458220944727
|View full text |Cite
|
Sign up to set email alerts
|

Online electronic healthcare records: Comparing the views of cancer patients and others

Abstract: This study investigates differences in attitudes towards, and experiences with, online electronic health records between cancer patients and patients with other conditions, highlighting what is characteristic to cancer patients. A national patient survey on online access to electronic health records was conducted, where cancer patients were compared with all other respondents. Overall, 2587 patients completed the survey (response rate 0.61%). A total of 347 respondents (13.4%) indicated that they suffered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Unsurprisingly, patients with more severe medical conditions (such as cancer) appear to access their health records more frequently. 36 In some, 37,38 but not all, 39 studies, patients reported symptoms of anxiety after accessing their medical records. In oncology, the most radical form of unrestricted access to EHRs by patients is to test reports (especially imaging results).…”
Section: The Subtle Burdens Of Patients' Unrestricted Access To Ehrs ...mentioning
confidence: 99%
“…Unsurprisingly, patients with more severe medical conditions (such as cancer) appear to access their health records more frequently. 36 In some, 37,38 but not all, 39 studies, patients reported symptoms of anxiety after accessing their medical records. In oncology, the most radical form of unrestricted access to EHRs by patients is to test reports (especially imaging results).…”
Section: The Subtle Burdens Of Patients' Unrestricted Access To Ehrs ...mentioning
confidence: 99%
“…In this first region-wide trial, the patients were offered access to their notes through an online patient portal called ‘Journalen’. 23 24 Then, in 2015, Journalen was launched as the national system in Sweden for online access to clinical notes. At the end of 2018, all regions had implemented Journalen and today, in a population of around 10 million, more than 4.5 million citizens have accessed their clinical notes.…”
Section: Background On Open Notesmentioning
confidence: 99%
“…Professional reluctance to raise awareness about access is also found in other countries. For example, in a survey of doctors in the USA, even after opening visit note summaries to patients, 78% (n=620) admitted that they did not encourage patients to read their documentation 30. Indeed, in a recent qualitative study among patients in England, participants reported that online access should be better promoted 17…”
Section: Discussionmentioning
confidence: 99%